Effect of palm oil on film formation and properties of natural rubber latex films - Ahmad K (Proceedings of the International Rubber Conference, Kobe, 1995; p39-42)
Palm oil in water emulsions prepared using different palm oils (OL, PO and ST) and a non-ionic emulsifier are added to NR latices and film physical properties studied. Results show that modulus and tensile strength of the films prepared from all types of latices decrease when OL diluent is present. The film mechanical properties are affected by the crystallinity of the stearin fraction of the oil. Prevulcanization of the latex prior to addition of oil emulsion caused significant deterioration of film tensile properties. Such detrimental effect is not obserrved if latex is mixed with the oil emulsion prior to prevulcanization.
Source Year: 1996
Keywords: Latex films; Natural rubber; Palm oil